Effect of Subcutaneous Injection of Sterile Water on Labor Pain, Type of Labor, and Satisfaction with Pain Management in Nulliparous Women - L Hosseini; S Najar; MH Haghighizadeh (Tehran University of Medical Sciences, 2010)
Background & Objective: Labor pain is usually the most severe pain women experience in their lives. Most women suffer from low back pain during first stage of labor. The pain can produce adverse effects on delivery procedure. Because of potential side effects of medications used in labor, alternative methods for pain relief have received more attention nowadays. The aim of this study was to evaluate the effect of subcutaneous injection of sterile water on labor pain, type of labor, and satisfaction with pain management in nulliparous women.Methods & Materials: This was a randomized single-blind study. Samples were consisted of 80 women who were randomly allocated to two intervention and control groups. In the intervention group (40 women) sterile water was injected subcutaneously in four sacral regions during first stage of labor. In the control group, we just inserted a needle in the same area. Low back pain intensity was assessed before and 10, 45, and 90 minutes after the injections using visual scales in both groups. Data were analyzed using descriptive (relative & absolute frequencies, mean and standard deviation) and inferential statistics (t-test, paired t-test and c2) in the SPSS.Results: There was no significant difference between two groups at baseline. The mean of pain intensity in 10 and 45 minutes after the injection was decreased significantly in the intervention group (P=0.00). There was no significant difference between two groups in the 90th minute. There was no difference in the type of labor between two groups. The mean of the satisfaction score was higher in the intervention group than in the control one.Conclusion: It seems that subcutaneous sacral injection of sterile water might be an effective and safe method to alleviate labor pain in women